PENGARUH RECEIVABLE TURN OVER, RASIO TUNGGAKAN, RASIO PENAGIHAN DAN AVERAGE COLLACTION PERIOD TERHADAP LABA PERUSAHAAN - Rizqiana Reza Rhomadhona; Ismunawan (Bajang Institute, 2022)
The purpose of implementing the following research is to get information about the effect of Receivable Turn Over, Average Collation Period, Arrears Ratio, and Billing Ratio to corporate profit. When conducting research, researchers used quantitative research methods to determine the sample by determining criteria according to the needs of researchers. There are 7 Go Public Multifinance Companies that have been listed on the Indonesia Stock Exchange which are sampled samples in the following research. The analysis tool used in research is multiple linear regression analysis. The acquisition of the results of analysis, the receivable turn over (RTO) has a positive influence on the company’s profit, the average collaction period (ACP) han a positive influence on insignificantly on the company’s profit, the ratio of the arrears has a positive and significant effect on the company’s profit, and the penagment ratio